Integrated tunable mode filter for a mode-division multiplexing system - Sun, Chunlei (2020)
Mode-division multiplexing (MDM) using multiple spatial modes as independent signals has been a promising technique to increase the communication capacity in conjunction with wavelength-division multiplexing (WDM). In MDM systems, mode filters are key components to filter out the undesired signals on specific mode. Analogous to a wavelength tunable filter used in a WDM system, here we propose and experimentally demonstrate a fundamental- or high-order-mode-pass tunable filter for a flexible MDM optical network based on a silicon platform. It consists of two switchable mode exchangers (MEs) and a fundamental-mode pass filter. By controlling the working state of the MEs, dynamic filtering and a tunable output can be achieved. This tunable mode filter exhibits a high extinction ratio of 18 dB and low insertion loss of 3 dB over the C-band. For further demonstration, the proposed device is tested using a modulated signal at 20 Gb/s. The eye diagrams and the bit error rates indicate a good filtering performance.